A small tally of future regrets - Pipe, Meghan, author; Levy, EJ, advisor; Doenges, Judy, committee member; Alexander, Ruth, committee member (Colorado State University. Libraries, 2018)
These eight short stories, told mainly but not exclusively from the perspectives of young women, portray work and relationships at a moment of cultural shift, at the start of the twenty-first century in America, when women are increasingly enfranchised, educated, and no longer defined by or economically dependent on relationships with men. In these stories, relationships among women—mothers and daughters, sisters, friends—take center stage as economies and gender norms change, while men are often relegated to a supporting role. As traditional scripts fail in this uncertain, often perilous world, these characters must look for new ones, even as they recognize the comforts of history and of structures that endure, from Granada's Alhambra to a still-working Long Island grist mill. Troubling the boundary between autobiography and fiction, these stories are told in a confessional, intimate voice in the tradition of Amy Hempel and Lorrie Moore, delighting in the tension between fact and fiction in a moment of transformation.